Characterization and pathogenicity of soil borne pathogens inducing root rot symptoms in common bean in Rwanda - Floride, Mukamuhirwa; Lewis, Butare; Albert, Ruhakana; Bellancile, Uzayisenga; Christine, Mukantwali; Augustin, Musoni; C., Mukankusi (International Journal of Scientific Research and Management (IJSRM), 2018)
Though Rwanda is among the highest common bean producers and consumers, this crop is still challenged by different factors including root rot diseases resulting in low yield potential. Root rot diseases can cause up to 100% of yield loss. Despite different soil borne pathogens causing bean root rot diseases; there is no recent literature that clearly documents the most aggressive ones affecting common beans in Rwanda. This study aimed at identifying the root rot pathogens affecting bean crop in Rwanda. A survey was conducted to collect bean samples showing root rot symptoms in 12 agro -ecological zones where bean crop is mostly grown. The selection of samples was based on the level of contamination and the purity of cultures. A total number of 132 samples were therefore selected and considered for further analysis. The pathogen isolation was done in Rubona at Rwanda Agriculture and Animal Resources Development Board (RAB) Biotechnology and Pathology laboratory. Structural characterization of soil borne pathogens was also carried out along with pathogenicity evaluation. The growth rate of identified pathogens were significantly different (P